INCREASING STUDENT EMPOWERMENT THROUGH ASENet - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
MEDAN, NORTH SUMATERA (INDONESIA), 6 June 2015 University students were urged to explore and be involved in a wide range of activities made available to them through empowerment including entrepreneurshiprelated educational and engagement activities.